BEST PRACTISE CHAIRMAN OF MUSYAWARAH GURU MATA PELAJARAN (MGMP) ECONOMY IN DEVELOPING THE PROFESSIONAL COMPETENCY OF ECONOMIC TEACHERS BANYUWANGI DISTRICT: HAKIKAT GURU ”KAYA” BEST PRACTISE KETUA MUSYAWARAH GURU MATA PELAJARAN (MGMP) EKONOMI DALAM PENGEMBANGAN KOMPETENSI PROFESIONAL GURU EKONOMI KABUPATEN BANYUWANGI - Kurnia Dewi (SOSIOEDUKASI, 2020)
Many factors can make a person successful as a "rich" teacher. The most important factor is the motivation to become a teacher that comes from within oneself. In responding to these challenges, it is natural that every educator and educational staff is motivated to improve professional abilities in their respective fields, It is hoped that through the MGMP activities, the professional ability of teachers will increase to the point of being truly professional. The Economic MGMP program is basically a major part of the development of the Economic MGMP. The program must always refer to efforts to increase teacher competence and professionalism. Human resources to support the activities of the Economic MGMP consist of primary resource persons and supporting resource persons. Management of the Economic MGMP as a forum for increasing competence and developing teacher professionalism includes planning, implementing, and evaluating the Economic MGMP program.